2017
DOI: 10.1186/s12864-017-3803-6
|View full text |Cite
|
Sign up to set email alerts
|

Systems-based approach to examine the cytokine responses in primary mouse lung macrophages infected with low pathogenic avian Influenza virus circulating in South East Asia

Abstract: BackgroundInfluenza A virus (IAV) is a major public health concern, being responsible for the death of approximately half a million people each year. Zoonotic transmissions of the virus from swine and avian origin have occurred in the past, and can potentially lead to the emgergence of new IAV stains in future pandemics. Pulmonary macrophages have been implicated in disease severity in the lower airway, and understanding the host response of macrophages infected with avian influenza viruses should provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
1
1
0
Order By: Relevance
“…Transcriptomic data showed metabolic genes, including Irg1, Ca2, Pfkfb3, and Hk2, among the top 100 most upregulated genes in alveolar MØ after IAV infection. This result was consistent with in vitro MØ studies in which IAV induced the expression of glycolytic metabolic genes concomitant to increased extracellular acidification associated with glycolysis 225. Switching from OXPHOS to glycolysis facilitates ROS production mediated by dedicated enzymes, such as NADPH oxidases.…”
supporting
confidence: 89%
“…Transcriptomic data showed metabolic genes, including Irg1, Ca2, Pfkfb3, and Hk2, among the top 100 most upregulated genes in alveolar MØ after IAV infection. This result was consistent with in vitro MØ studies in which IAV induced the expression of glycolytic metabolic genes concomitant to increased extracellular acidification associated with glycolysis 225. Switching from OXPHOS to glycolysis facilitates ROS production mediated by dedicated enzymes, such as NADPH oxidases.…”
supporting
confidence: 89%
“…Following infection with various IAV strains, excessive levels of inflammatory mediators and widespread tissue damage can be observed in the lung, a target tissue for respiratory viruses ( Jang et al, 2012 ; Burggraaf et al, 2014 ; Herold et al, 2015 ; Taye et al, 2017 ). Moreover, several studies have shown that neurotropic and even non-neurotropic IAV infections lead to the release of inflammatory mediators in the brain ( Jang et al, 2012 ; Jurgens et al, 2012 ; Hosseini et al, 2018 ; Düsedau et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%